Applied body composition assessment - Heyward, Vivian H.; Stolarczyk, Lisa M. (Human Kinetics, 2004)
Brings both practitioners and students up to date on the latest body composition methods and equations for healthy and clinical populations. Like the popular first edition, this book addresses the principles underlying the skinfold, bioelectrical impedance, near-infrared interactance, and anthropometric methods of body composition assessment. It also shows the reader how to control for potential errors in measurement, different equations for different populations, and much more